Phylogenetic analysis of sea cucumbers (Echinodermata: Holothuroidea) in Malaysia as inferred from Cytochrome C Oxidase I MtDNA - Hussin, Rosnah; Kamarudin, Kamarul Rahim; Nordin, Noor Faizul Hadry; Hashim, Ridzwan; Mohammad , Mohd Nahar (2006)
Diverse species of sea cucumber (Echinodermata: Holothuroidea) were documented in Malaysia. Their abundance benefits the Malaysians in traditional and modern medicinal industry as well as in food processing industry. Previously, the identification of sea cucumber species in Malaysia was done mainly based on morphological characters. Among the characters used were the shapes of ossicles, body shapes and colour, shapes of tentacles, the existence and shapes of papillae. However, the morphological approaches were unsuccessfully unravelled the problematic taxonomic status of sea cucumbers as there are unidentified and unknown species present throughout Malaysia to date. As an alternative approach to verify the species status inferred from morphology, molecular ecology analyses were incorporated in this study to examine the phylogenetic relationship between and among selected species of sea cucumbers from Malaysia by using cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene. Three genera were selected namely Holothuria and Stichopus from order Aspidochirotida, and genus Molpadia from order Molpadiida. Polymerase Chain Reaction (PCR) gave the desired products of amplified COI mtDNA region with length of approximately 510 bp. After the multiple sequence alignment, partial sequences of COI mtDNA gene ranging from 488 bp to 489 bp were utilized for further analyses. 22 ingroups of sea cucumbers and one outgroup represented by Diadema setosum were included in the reconstruction of neighbour-joining (NJ) tree and maximum parsimony (MP) tree. Base frequency and genetic distance based on Kimura-2 parameter model were also calculated prior to the reconstruction of phylogenetic tree. Basically, both types of phylogenetic trees suggest the paraphyly of Holothuria and Stichopus due to the clustering of four Stichopus horrens individuals together with Holothuria species. Apart from that, Molpadia species seems genetically close to the main group of genus Holothuria and Stichopus horrens. The phylogenetic results were also supported by the data from genetic distance. Overall, the above findings strongly suggest that the grouping and classification at species and higher level as inferred from COI mtDNA gene are unresolved, requiring further molecular ecology studies to be done in the near future.